Comparison of the biomechanical effect of distal implants placed at different angles in the all-on-four technique: A nonlinear finite element analysis - Unuvar, Yildiz; Calis, Aylin; Koc, Osman (ELSEVIER, 2025)
Introduction: The All-on-four technique addresses this by placing two vertical implants in the anterior region and two posterior implants angled up to 45 degrees. This study evaluates stress distribution on bone, implants, abutments, gingiva, and prostheses based on posterior implant angulation, using both standard and angled neck implants. Additionally, angled neck implants were used alongside standard implants. Methods: To evaluate the biomechanical stress and displacement behavior of implants placed at 15 degrees, 30 degrees, 45 degrees, and 30 degrees neck-angled in the interforaminal region of using the All-on-four technique, under a 200 N masticatory force on bone, implant, abutment, and prosthesis, using the FEA method with a nonlinear solver. Results: The stress values measured in the neck region of the angled implant and abutment placed in the distal region were highest in model IV (305 and 420 MPa), followed model III (282 and 359 MPa), model II (192 and 337 MPa) and lowest in model I (177 and 225 MPa), respectively. The mean elemental von Mises stress in the mandibular bone region where the implant was placed was highest in model I (56 MPa) and lowest in model III (40.4 MPa). Conclusion: As the angle of insertion of the implant into the bone increases, the biomechanical stress value on the implant and abutment also increases. Among the models, the lowest von Mises stress values on the implant and abutment were measured in model I and model II. Models with low stress values can be recommended for patients with clinical conditions and biomechanical risk factors. (c) 2024 Elsevier Masson SAS. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: All-on-four; Neck angled implant; Straight implant; Multiunit abutment; Finite element analysis; Stress; PTERYGOMAXILLARY DISJUNCTION; STRESS-DISTRIBUTION; EXPANSION; PATTERNS; SITES; Dentistry, Oral Surgery & Medicine